أثر الآلهة في أدب بلاد الرافدين في ضوء النصوص المسمارية - المتولي نوالة أحمد محمود; المعموري فاطمة عباس (Al-Adab Journal, 2019)
Moreover, The religion is an important factor that called man to work and seek to find everything that pleases the gods to avoid anger and win the satisfaction of believing that this thing that will make him happy in his life, and this brings us to the important fact is the truth of his faith and belief then for this we can promise Religion is a positive factor that led to the arrival of man to know many aspects of civilization, such as architecture, literature and artistic and intellectual achievements, and this absolute faith in the goddess make it puts its touches in all steps military victories and construction of urban projects and construction of cities, planting land, and put it to law and writing literature and poetry His quest for the emergence of the fullest image in the eyes of God to gain satisfaction.